A hybrid nanomaterial with NIR-induced heat and associated hydroxyl radical generation for synergistic tumor therapy. (April 2019) - Zhang, Cheng; Liu, Wen-Long; Bai, Xue-Feng; Cheng, Si-Xue; Zhong, Zhen-Lin; Zhang, Xian-Zheng
Abstract: Although photothermal therapy (PTT) and photodynamic therapy (PDT) are widely commended for tumor treatment recently, they still suffer severe challenges due to the non-specificity of photothermal agents (PTAs)/photosensitizers (PSs) and hypoxic tumor microenvironment. Here, an oxygen independent biomimetic nanoplatform based on carbon sphere dotted with cerium oxide and coated by cell membrane (MCSCe) was designed and synthesized with good biocompatibility, homologous targeting ability, and improved photophysical activity. Notably, MCSCe could realize accumulation of hydrogen peroxide (H2 O2 ) in tumor cells and hyperthermia under single laser (808 nm) irradiation, which were simultaneously utilized by itself to produce more toxic hydroxyl radical (OH). Resultantly, the synergistic therapeutic effect against tumor cells was obtained under near infrared (NIR) laser irradiation. Graphical abstract: Carbon sphere dotted with cerium oxide and coated by cancer cell membrane could effectively promote the accumulation of H2 O2 in tumor cells, and obtain excellent synergistic therapeutic effect against solid tumors.Image 1